El uso de las TICS en el procesamiento y comunicación de la información y su influencia en el desempeño docente - Fajardo León, Joselyn Lilibeth (2020)
This case study was carried out with the theme of: The use of tics in the processing and communication of information and its influence on the teaching performance of the Educational Unit October 11, Urdaneta canton, Los Ríos province; Being this an institution, that fulfills to fortify and potentiate the human talent of the community, and the country. To advance this research, the deductive method was used, which uses general principles based on the particular facts in the problem to be investigated. Through a survey that was carried out in this campus in such a way that it helped to collect fundamental information on the performance of the teacher, on the knowledge of tics and the proper management of these tools, whose objective is to establish the influence that the use of the tics in teachers. The results obtained in this case study reveal that the little knowledge and functionality of tics leaves as a consequence the scarcity of teacher performance.